Peran sosiologi pendidikan terhadap interaksi sosial siswa di Sekolah - Ilham, Muhammad Nur; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Social interaction is an activity carried out by two or more individuals that results in mutual responses or feedback. This article discusses how sociology plays a role in students’ social interactions at school. The focus of this research is to understand the concept of educational sociology in relation to students’ social interactions at school, to identify the factors that influence these interactions, and to describe the forms of student interaction that demonstrate the role of educational sociology in school life. The research method used is library research or a literature review, which involves analyzing, reading, and collecting data from various relevant academic articles.